2016
DOI: 10.3389/fpsyg.2016.01960
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Spatial Perception without Vision

Abstract: Valuable insights into the role played by visual experience in shaping spatial representations can be gained by studying the effects of visual deprivation on the remaining sensory modalities. For instance, it has long been debated how spatial hearing evolves in the absence of visual input. While several anecdotal accounts tend to associate complete blindness with exceptional hearing abilities, experimental evidence supporting such claims is, however, matched by nearly equal amounts of evidence documenting spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 95 publications
3
36
1
5
Order By: Relevance
“…Similar results were found in the auditory domain, with a majority of studies showing enhanced auditory processing in blind individuals (Lessard et al 1998;Gougoux et al 2004;Voss et al 2004;Focker et al 2012;Voss and Zatorre 2012;Collignon et al 2013;Lewald 2013;Jafari and Malayeri 2014;Kattner and Ellermeier 2014;Cornell Karnekull et al 2016;Nilsson and Schenkman 2016;Kolarik et al 2017) and some studies reporting impaired performance on auditory tasks (Gori et al 2014;Finocchietti et al 2015;Menard et al 2015;Cappagli and Gori 2016;Voss 2016), or no difference from sighted participants (Collignon et al 2011;Voss and Zatorre 2012;Collignon et al 2013). These different results may depend on the specific task requirements (King 2014), or may reflect a trade-off between different auditory abilities (Voss et al 2015).…”
Section: Introductionsupporting
confidence: 61%
“…Similar results were found in the auditory domain, with a majority of studies showing enhanced auditory processing in blind individuals (Lessard et al 1998;Gougoux et al 2004;Voss et al 2004;Focker et al 2012;Voss and Zatorre 2012;Collignon et al 2013;Lewald 2013;Jafari and Malayeri 2014;Kattner and Ellermeier 2014;Cornell Karnekull et al 2016;Nilsson and Schenkman 2016;Kolarik et al 2017) and some studies reporting impaired performance on auditory tasks (Gori et al 2014;Finocchietti et al 2015;Menard et al 2015;Cappagli and Gori 2016;Voss 2016), or no difference from sighted participants (Collignon et al 2011;Voss and Zatorre 2012;Collignon et al 2013). These different results may depend on the specific task requirements (King 2014), or may reflect a trade-off between different auditory abilities (Voss et al 2015).…”
Section: Introductionsupporting
confidence: 61%
“…Findings of the previous literature evidence are in accordance with the perceptual enhancement hypothesis, that is VIPs and blind people will attempt to develop the ability of other senses to compensate for visual impairment [42], [43]. A recent survey concluded that complete blind people at an early stage show the superior performance in spatial hearing in the horizontal plane, but the performance in the vertical plane is unsatisfactory [44]. The spatial sound resolution ability of blind people is relatively low when they use the allocentric frame of reference.…”
Section: Auditionsupporting
confidence: 68%
“…Taken together, these results suggest that if vision is absent or degraded, tactile feedback is insufficient to calibrate auditory distance in peripersonal space, corresponding to "near" space in the current results. The ability to judge the distance of a single, static sound source is relatively poor compared to the ability to judge the azimuth of a sound in normally sighted individuals 59 as well as blind individuals 5,16 . Although it is unclear why tactile and audiomotor feedback appear to be sufficient to calibrate internal representations of sound azimuth but not distance, one possible explanation is that small changes in sound azimuth cues are easier to detect than small changes in auditory distance cues, rendering azimuth cues but not distance cues amenable to calibration by tactile or audiomotor feedback.…”
Section: Discussionmentioning
confidence: 99%
“…For example, blindness often results in dramatic improvements in echolocation skills 4,8 and the ability to locate sounds in azimuth (left-front-right judgments) 9,10 , but leads to significantly poorer ability to judge the vertical position of sounds 11,12 , or judge sound position with respect to external acoustic landmarks 13 . It has been suggested that the changes underlying enhanced performance are fundamentally related to adaptations within the occipital cortex, where visual areas of the brain are recruited to process auditory inputs in the event of visual loss 5,14,15 . However, the underlying principles of what drives changes in auditory abilities following visual loss are not well understood.…”
mentioning
confidence: 99%